Technical and Vocational Education and Training in Workforce Development (Journal of Training and Development, 2015)
There are many contributions of Technical and Vocational Education and Training (TVET) on a nation’s economy. TVET has been proved as the key for skill development. With its feature focused on specific occupation, it has allowed individuals to find skill related jobs or start own employment. TVET stands a major player in economic growth of a nation through development of workforce and rise in employment rate. On one hand, TVET’s role stands on employment generation in the job market while on the other hand, TVET is regarded more significant to promote self employment where employment opportunities are scare and individuals are enrolled in informal or agricultural sector. This paper tries to explore different contributions of TVET on employment in the labour market and in uplifting self employment through the development of relevant skills and the different kinds of contributions it gives and importance it holds depending upon the economic development of the nations.DOI: http://dx.doi.org/10.3126/jtd.v1i0.13094 Journal of Training and Development Vol.1 2015: 77-84